Highly regioselective opening of zirconacyclopentadienes by remote coordination: concise synthesis of the furan core of the leupyrrins - Debnar, Thomas; Dreisigacker, Sandra; Menche, Dirk (Chemical communications, 2013)
An efficient protocol for the highly regioselective opening of aliphatic zirconacyclopentadienes is reported. The one-pot process involves a zirconocene-mediated cyclization of 1,6-diynes and highly selective cleavage of the metallacycles with NBS and enables a concise synthesis of the tetrahydrofuran-core of the leupyrrins.